Design issues of an IPM motor for EPS - Wang, Can-Fei; Shen, Jian-Xin; Luk, Patrick Chi-Kwong; Fei, Wei-Zhong; Jin, Meng-Jia (Emerald Group Publishing Limited, 2011)
In electric power steering (EPS), permanent magnet (PM) brushless ac (BLAC) motors offer distinct advantages over other electric motor types in terms torque smoothness, reliability and efficiency. The design procedure of an interior permanent magnet (IPM) motor used in EPS is presented in this paper. The requirements of the steering system are first introduced, and the machine's specifications are then derived. Critical issues which have considerable impacts on the machine's performance, such as operation mode, rotor structure and slot/ pole combination, are analyzed. Subsequently, a 12-slot/10-pole sinusoidally excited IPM machine with concentrated windings is proposed and optimized based on finite element analysis (FEA) modelling. The losses and efficiency are then computed. Performance predictions from the FEA results confirm all the requirements are met or exceeded. A prototype motor has been built for validation.
Keywords: Electric power steering; Interior permanent magnet; Motor design; Finite element analysis; Road vehicles